TP53 mutations in myelodysplastic syndrome are strongly correlated with aberrations of chromosome 5, and correlate with adverse prognosis. (9th January 2013) - Kulasekararaj, Austin G.; Smith, Alexander E.; Mian, Syed A.; Mohamedali, Azim M.; Krishnamurthy, Pramila; Lea, Nicholas C.; Gäken, Joop; Pennaneach, Coralie; Ireland, Robin; Czepulkowski, Barbara; Pomplun, Sabine; Marsh, Judith C.; et al.
Summary This study aimed to determine the incidence/prognostic impact of TP53 mutation in 318 myelodysplastic syndrome (MDS) patients, and to correlate the changes to cytogenetics, single nucleotide polymorphism array karyotyping and clinical outcome. The median age was 65 years (17–89 years) and median follow‐up was 45 months [95% confidence interval (CI) 27–62 months]. TP53 mutations occurred in 30 (9·4%) patients, exclusively in isolated del5q (19%) and complex karyotype (CK) with ‐5/5q‐(72%), correlated with International Prognostic Scoring System intermediate‐2/high, TP53 protein expression, higher blast count and leukaemic progression. Patients with mutant TP53 had a paucity of mutations in other genes implicated in myeloid malignancies. Median overall survival of patients with TP53 mutation was shorter than wild‐type (9 versus 66 months, P < 0·001) and it retained significance in multivariable model (Hazard Ratio 3·8, 95%CI 2·3–6·3, P < 0·001). None of the sequentially analysed samples showed a disappearance of the mutant clone or emergence of new clones, suggesting an early occurrence of TP53 mutations. A reduction in mutant clone correlated with response to 5‐azacitidine, however clones increased in non‐responders and persisted at relapse. The adverse impact of TP53 persists after adjustment for cytogenetic risk and is of practical importance in evaluating prognosis. The relatively common occurrence of these mutations in two different prognostic spectrums of MDS, i.e. isolated 5q‐ and CK with ‐5/5q‐, possibly implies two different mechanistic roles for TP53 protein.